Poiesis Nucleus: an interinstitutional construction to strengthen studies and practices on occupational therapy and work - Souza, Marina Batista Chaves Azevedo de; Barroso, Bárbara Iansã de Lima; Alonso, Carolina Maria do Carmo; Nogueira, Lilian de Fatima Zanoni; Oliveira, Priscilla Viégas Barreto de; Silva, Talita Naiara Rossi da; Rodrigues, Daniela da Silva (Revista de Terapia Ocupacional da Universidade de São Paulo, 2022)
The Poiesis Nucleus - Interinstitutional Laboratory of Occupational Therapy and Work was born from the desire to set collective actions, inter-institutional partnerships, and academic dialogues between professors and occupational therapists that study work. This experience report describes the Nucleus building process. Also, it presents a profile of its researchers' members, productions, partnerships, future projects, and the contributions of this group to the studies and practices about occupational therapy and work. As a collective, the productions have summed up to two papers, four book chapters, inter-institutional partnerships in teaching, research, and extension activities, and debates about Occupational Therapy and work in academic events, with the leading professional's institutions in the country. It is concluded that the collective experience of peers promoted a dialogue between universities spread throughout the national territory, which is essential to promote exchanges of experiences, knowledge, and practices in the work field and Occupational Therapy.